The martial origins of democracy: a global study of military conscription and suffrage extensions since the Napoleonic wars. Issue 4 (19th May 2018) - Ingesson, Tony; Lindberg, Mårten; Lindvall, Johannes; Teorell, Jan
ABSTRACT: This article examines the relationship between conscription (the compulsory enlistment of civilians for military service) and democracy. Using the best available cross-country comparable data on the history of conscription and democracy, we demonstrate that there is an empirical relationship between conscription and democratization, but the relationship is more complicated than commonly believed. Specifically, we find that conscription increases the likelihood of male suffrage extensions, but only in wartime (when the conscript army is mobilized). We find no relationship between conscription and democratization apart from extensions of suffrage. Nor do we find support for the hypothesis that conscription shelters democracies from coups.